Fabrication and Upconversion Photoluminescence of CaMoO4: Er3+, Yb3+ Particles by A Cyclic Microwave-Assisted Metathetic Method - Sung Lim, Chang (Asian Journal of Chemistry, 2012)
Well-crystallized Er3+/Yb3+ co-doped CaMoO4 (CaMoO4:Er3+/Yb3+) particles were successfully synthesized via a cyclic microwave-assisted metathetic method, followed by further heat-treatment at 600 ºC for 3 h, showing a fine and homogeneous morphology with sizes of 0.2-1 μm. With excitation at 980 nm, CaMoO4:Er3+/Yb3+# exhibited a strong 525-nm emission band and a weak 550-nm emission band in the green region and a weak 655-nm emission band in the red region. The Raman spectra of CaMoO4:Er3+, CaMoO4:Er3+/Yb3+, CaMoO4:Er3+/Yb3+# and CaMoO4:Er3+/Yb3+## particles indicated that the additional strong peaks at higher frequencies (618, 575, 492, 420 and 373 cm-1) and at lower frequencies (290 and 234 cm-1).